2006
DOI: 10.1074/jbc.m512847200
|View full text |Cite
|
Sign up to set email alerts
|

RalA-exocyst-dependent Recycling Endosome Trafficking Is Required for the Completion of Cytokinesis

Abstract: In eukaryotic cells, recycling endosome-mediated trafficking contributes to the completion of cytokinesis, in a manner under the control of the centrosome. We report that the exocyst complex and its interacting GTPase RalA play a critical role in this polarized trafficking process. RalA resides in the recycling endosome and relocates from the pericentrosomal region to key cytokinetic structures including the cleavage furrow, and later, the abscission site. This event is coupled to the dynamic redistribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 39 publications
5
92
3
Order By: Relevance
“…In metazoans, Ral GTPases (RalA and RalB) interact with both Sec5 and Exo84, and these interactions have been implicated in many processes, including cell migration, autophagy, neurogenesis and cancer (Brymora et al, 2001;Sugihara et al, 2002;Moskalenko et al, 2002Moskalenko et al, , 2003Polzin et al, 2002;Balakireva et al, 2006;Bodemann et al, 2011;Chen et al, 2006Chen et al, , 2007Chien et al, 2006;Hazelett et al, 2011;Lalli, 2009;Rosse et al, 2006). Cell fractionation studies have shown that Sec5 and Exo84 are in separate sub-complexes (Moskalenko et al, 2003), and structure analysis has demonstrated that Sec5 and Exo84 competitively bind to GTP-Ral (Jin et al, 2005).…”
Section: Ralmentioning
confidence: 99%
See 1 more Smart Citation
“…In metazoans, Ral GTPases (RalA and RalB) interact with both Sec5 and Exo84, and these interactions have been implicated in many processes, including cell migration, autophagy, neurogenesis and cancer (Brymora et al, 2001;Sugihara et al, 2002;Moskalenko et al, 2002Moskalenko et al, , 2003Polzin et al, 2002;Balakireva et al, 2006;Bodemann et al, 2011;Chen et al, 2006Chen et al, , 2007Chien et al, 2006;Hazelett et al, 2011;Lalli, 2009;Rosse et al, 2006). Cell fractionation studies have shown that Sec5 and Exo84 are in separate sub-complexes (Moskalenko et al, 2003), and structure analysis has demonstrated that Sec5 and Exo84 competitively bind to GTP-Ral (Jin et al, 2005).…”
Section: Ralmentioning
confidence: 99%
“…In Arabidopsis, the exocyst subunits are localized to the separation sites during initiation of the cell plate and maturation, when vesicle fusion is in high demand (Fendrych et al, 2010). In mammalian cells, the exocyst is involved in the trafficking of secretory vesicles to the cleavage furrow and midbody under the control of Rab11 and RalA (Chen et al, 2006;Fielding et al, 2005;Neto et al, 2013). Because cleavage often takes place at one side of the midbody (also known as asymmetric abscission), the vesicles appear to be recruited to the cleavage site of one of the daughter cells (Gromley et al, 2005;Schiel et al, 2013).…”
Section: The Exocyst In Cytokinesismentioning
confidence: 99%
“…The vesicle-associated GTPase Sec4p binds to the exocyst protein Sec15p, potentially linking vesicles to the complex and thereby to the fusion site (Guo et al, 1999). In higher organisms, the exocyst has also been shown to be required for late stages of cytokinesis (Cascone et al, 2008;Chen et al, 2006;Fielding et al, 2005;Gromley et al, 2005). Additionally, the exocyst complex defines areas of membrane addition in neuronal growth cones and developing Drosophila oocytes (Dupraz et al, 2009;Hazuka et al, 1999;Murthy and Schwarz, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These data are further supported by functional interactions between exocyst components and proteins known to regulate abscission. For example, RalA and RalB interact with Sec5 and Exo84, respectively (Cascone et al, 2008;Chen et al, 2006). The interaction of RalB and Exo84 induces the assembly of a complex of beclin and the mammalian phosphatidylinositol 3-kinase Vps34 on nascent autophagosomes (Bodemann et al, 2011), which is potentially important for cytokinesis, because beclin and Vps34 are also implicated in this process (Sagona et al, 2010;Thoresen et al, 2010).…”
Section: Membrane-tethering Complexes In Cytokinesismentioning
confidence: 99%